2006
DOI: 10.1007/s10165-006-0525-z
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrotic effects of hepatocyte growth factor on scleroderma fibroblasts and analysis of its mechanism

Abstract: We investigated the effect of hepatocyte growth factor (HGF) on collagen metabolism in cultured fibroblasts from scleroderma (SSc) patients and discussed the possible mechanism of its effect. Synthesis of matrix metalloproteinase-1 (MMP-1) and collagen and mRNA levels of various cytokines were examined by enzyme-linked immunosorbent assay and real-time polymerase chain reaction, respectively. Hepatocyte growth factor enhanced MMP-1 production and mRNA levels of MMP-1 and Ets-1 (a transcriptional factor of MMPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
(35 reference statements)
1
15
0
Order By: Relevance
“…Recently, Ets-1 has been shown to modulate the transcription of ECM genes, including type I collagen (CzuwaraLadykowska et al, 2002;Sherriff-Tadano et al, 2006). Constitutive expression of Ets proteins has been associated with cellular transformation of erythroblasts and fibroblasts (Kola et al, 1993;Iwasaka et al, 1996;Reisdorff et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Recently, Ets-1 has been shown to modulate the transcription of ECM genes, including type I collagen (CzuwaraLadykowska et al, 2002;Sherriff-Tadano et al, 2006). Constitutive expression of Ets proteins has been associated with cellular transformation of erythroblasts and fibroblasts (Kola et al, 1993;Iwasaka et al, 1996;Reisdorff et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Several potential binding sites for transcription factors, such as members of the Ets family, are located in the collagen promoter, and it is thought that these factors are associated with collagen gene expression (Znoyko et al, 2006;Peng et al, 2008). Czuwara-Ladykowska et al (2002) reported that elevated expression of Ets-1 altered TGF-b induction of type I collagen and other matrix-related genes in human fibroblasts (Sherriff-Tadano et al, 2006), showing that Ets-1 may act as an antagonist of the profibrotic effect of TGF-b. It is known that overexpression of Ets-1 in cultured mesangial cells suppresses the TGF-b-induced reduction of DNA-binding activity (Mizui et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been suggested that HGF (hepatocyte growth factor) exerts antifibrotic effects, via the c-met receptor and TGF-β1 inhibition [96], or through peroxisome proliferator-activated receptor- (PPAR)γ agonists [97], among other mechanisms, dependently or independently of TGF-β [98, 99]. It has been shown that local administration of HGF gene enhances the regeneration of dermis and minimizes scarring in acute incisional wounds in an experimental model [100].…”
Section: Human Recombinant Tgf-β3 and Tgf-β Superfamily-related Prmentioning
confidence: 99%